Enhanced anti-HIV functional activity associated with Gag-specific CD8 T-cell responses. - Julg, B; Williams, K; Reddy, S; Bishop, K; Qi, Y; Carrington, M; Goulder, P; Ndung'u, T; Walker, B (2010)
Effective HIV-specific T-cell immunity requires the ability to inhibit virus replication in the infected host, but the functional characteristics of cells able to mediate this effect are not well defined. Since Gag-specific CD8 T cells have repeatedly been associated with lower viremia, we examined the influence of Gag specificity on the ability of unstimulated CD8 T cells from chronically infected persons to inhibit virus replication in autologous CD4 T cells. Persons with broad (>or=6; n = 13) or narrow (